2009
DOI: 10.1073/pnas.0904729106
|View full text |Cite
|
Sign up to set email alerts
|

The structure of DNA overstretched from the 5′5′ ends differs from the structure of DNA overstretched from the 3′3′ ends

Abstract: It has been suggested that the structure that results when doublestranded DNA (dsDNA) is pulled from the 3 3 ends differs from that which results when it is pulled from the 5 5 ends. In this work, we demonstrate, using phage dsDNA, that the overstretched states do indeed show different properties, suggesting that they correspond to different structures. For 3 3 pulling versus 5 5 pulling, the following differences are observed: (i) the forces at which half of the molecules in the ensemble have made a complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
94
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 36 publications
14
94
2
Order By: Relevance
“…Single molecule pulling experiments (SMPE) [7][8][9][10][11] and simulation studies [9,[12][13][14][15][16][17][18][19][20][21] revealed that the canonical form of double stranded DNA (B-DNA) stretches almost twice its original contour length when subjected to stretching forces. Experimental studies [7][8][9][22][23][24][25][26][27] report an overstretched transition of B-DNA when pulled with force ranging between 60 − 70 pN, and the double strands separate at sufficiently high forces [28]. A characteristic plateau has been observed in the force-extension curve of dsDNA that signifies a highly cooperative transition from B-DNA to an overstretched conformation [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single molecule pulling experiments (SMPE) [7][8][9][10][11] and simulation studies [9,[12][13][14][15][16][17][18][19][20][21] revealed that the canonical form of double stranded DNA (B-DNA) stretches almost twice its original contour length when subjected to stretching forces. Experimental studies [7][8][9][22][23][24][25][26][27] report an overstretched transition of B-DNA when pulled with force ranging between 60 − 70 pN, and the double strands separate at sufficiently high forces [28]. A characteristic plateau has been observed in the force-extension curve of dsDNA that signifies a highly cooperative transition from B-DNA to an overstretched conformation [9].…”
Section: Introductionmentioning
confidence: 99%
“…Using constant force SMPE on λ-phage DNA, Danilowicz et al [25] reported that DNA becomes more stable with OS3 pulling than with OS5 pulling and further pointed out the differences between structures obtained from two different pulling protocols. They observed a narrow backbone spacing and rotated bases for the OS5 overstretched structure.…”
Section: Introductionmentioning
confidence: 99%
“…In Experiment 1, the forceresponse of overstretched DNA is inconsistent with that of one ssDNA strand or two noninteracting ssDNA strands (18,19). In Experiment 2, a second transition at an even higher force has frequently been observed that leads to final strand separation after the 65-pN overstretching transition (19)(20)(21)(22). The existence of this second transition, which is definitely a melting transition, supports the notion that the first transition (at approximately 65 pN) is not a melting transition (19)(20)(21).…”
mentioning
confidence: 99%
“…To test this prediction, Shokri et al (16) used glyoxal modification of the DNA base pairs exposed during overstretching to show that the base pairs were indeed exposed to solution during overstretching. However, even this structural evidence was questioned as allegedly occurring because of nicks in the DNA backbone (17). Thus, despite many years of detailed study, DNA stretching experiments lacked See companion article on page 18231.…”
mentioning
confidence: 99%